The Effect of Presto Processing Time To Shredded Quality Chirocentrus dorab - Sari, N. Ira; ', Purwanda; ', Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The purpose of this research was to determine the effect of presto processing time to Chirocentrus dorab shredded quality. The methode used in this research was experimental with different of presto processing time of Chirocentrus dorab shredded processing. Based on parameter tested, the best treatment was 75 minutes of presto processing time with brown yellowish of appearance (8.96), dried, similar and very softly of fibrous texture (8.64), very fragrant aroma, specific fish shredded (8.76), very good, fish and seasoning taste (8.96); water content (4.22%), fat content (16.20%), protein content (39.78%), ash content (4.17%), total plate count (4.4 x 102 cell/gram), and calcium content (3.81%).Keywords: Chirocentrus dorab, presto, shredded